Prosperity and Poverty in the Bible: Search for Balance - Asamoah-Gyadu, J. Kwabena (Lausanne Movement, 2015)
Preamble: Expensive Christianity Come, all you who are thirsty, come to the waters; and you who have no money, come, buy and eat! Come buy wine and milk without money and without cost (Isaiah 55:1). Christianity has become economically expensive in Africa today and that is partly because of the shortfalls in what has come…
free